ESG dan Kinerja Keuangan: Studi Moderasi Ukuran Perusahaan pada Perusahaan Terdaftar di Bursa Efek Indonesia - Adriel Abie Kristia; Hersugondo Hersugondo (Faculty of Economics and Business Diponegoro University, 2025)
This study examines the relationship between ESG and company performance in companies listed on the Indonesia Stock Exchange during the period 2018–2023. This research focuses on ESG performance represented by the ESG score and firm size as a moderator.The sample used was taken from 59 companies from various sectors that have complete data during the period 2018–2023. The data collection technique in this study used purposive sampling. Data processing in this study was conducted using moderated regression analysis.The findings of this study indicate that ESG scores have a positive relationship with the financial performance of the company. These findings are consistent with legitimacy theory. Furthermore, firm size strengthens the relationship between ESG and the company's financial performance